Pengaturan Menu Makanan dengan Meminimalkan Lemak Menggunakan Pemrograman Linear - Yeni Rokhayati (Politeknik Negeri Batam, 2014)
The selection of good menu from different types of foods, certainly not an easy doing. In this study, the menu selection that meet the daily nutritional requirements, and also low in fat, approximated using linear programming concepts. The nutritions to be considered are calorie, protein, fat, carbohydrates, calcium, phosphorus, iron, vitamin A, vitamin B1 and vitamin C. A sample of diet menu selection is applied. The result is, from a variety of foods available obtained menus that meet nutritional requierements and have a minimum fat content.